CORRELATION OF ACTIVE PARTICIPATION WITH MATHEMATICS LEARNING OUTCOMES OF GRADE 2 STUDENTS ON PLACE VALUE MATERIAL - Triana Zahroh; Rintis Rizkia Pangestika; Ageng Triyono (Jurnal Cakrawala Pendas, 2026)
The background of this study is based on the low achievement of students in understanding place value concepts, which is presumed to be related to the lack of active engagement during learning. This study aims to analyze the relationship between students' active participation and mathematics learning outcomes on place value material in Grade 2 of SDN 1 Pangenrejo. The research employed a quantitative approach using a correlational survey method. All Grade 2 students (N = 31) were included as the sample through total sampling. Data on active participation were collected using a standardized observation sheet, while learning outcomes were measured using a validated written test. Data analysis was conducted using the Spearman Rank correlation test because the data were not normally distributed. The results indicated that the relationship between students' active participation and mathematics learning outcomes was very low and not statistically significant. These findings suggest that student activeness in learning, particularly behavioral participation, does not necessarily reflect deep conceptual understanding; therefore, active participation alone is insufficient to improve mathematics learning outcomes. Other factors such as motivation, instructional strategies, and the role of teachers also contribute to learning outcomes. This study recommends the diversification of instructional strategies and the strengthening of teachers' roles in creating meaningful learning experiences. Further research with broader scope and variables is strongly recommended to enrich the understanding of factors influencing mathematics learning success in elementary schools.